Language, Law, And Ethnicity In Tamil Communities: A Comparative Study of Tamil Nadu And Northern Sri Lanka - Lakshithaa, S.D.; Swathi, S. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
Language policies and legal frameworks play a critical role in multi-ethnic societies by shaping ethnic identities and influencing inclusion, marginalization, and resistance. Policies such as India’s Official Languages Act of 1963 and Sri Lanka’s Sinhala-Only Act of 1956 have exacerbated ethnic tensions, by establishing language hierarchies. Tamil literature, used as a medium of resistance has since been advocating for linguistic rights and influenced policy reforms, emphasising its role in addressing ethnic conflicts. While existing research focuses on the political and historical implications of linguistic policies, it often overlooks the combined influence of Ethnic Conflict Theory, Legal Pluralism, and Cultural Nationalism on identity formation and reconciliation. This study addresses the above gap by focusing on Tamil Nadu and Northern Sri Lanka, where both regions have connecting factors of Tamil heritage and linguistic commonalities but have had distinct political and legal outcomes. These differences make the case studies ideal for understanding language’s role in shaping ethnic relations. The objective of the research is primarily to explore the nuances of how language policies and legal frameworks have shaped Tamil ethnic identity and assess the Tamil literature's contribution to resisting linguistic hegemony and advocating for reform. The research employs a qualitative comparative case study approach with thematic deductive analysis to examine sources such as the Tamil Official Language Act of 1956, the Sinhala-Only Act of 1956, and literary works from eminent poets like Bharathiyar, Periyar and writings by N.A. Nuhman and Neelavanan. The research findings show that Tamil Nadu’s linguistic reforms, supported by regional autonomy have reinforced cultural pride and political stability, while Sri Lanka’s policies, despite progress, left unresolved grievances. The study highlights the role of inclusive language policies and cultural advocacy in resolving the issues of ethnic conflicts and fostering reconciliation in diverse multi-ethnic societies.
Keywords: Language policies; Ethnic Conflict Theory; Legal Pluralism; Cultural nationalism and reconciliation